Engineering characteristics of water-bearing weakly cemented sandstone and dewatering technology in tunnel excavation. (March 2022) - Zhao, Jinpeng; Tan, Zhongsheng; Wang, Xiuying; Zhou, Zhenliang; Li, Guoliang
Highlights: Water bearing weakly cemented sandstone has been studied by laboratory test method. The relationship between mechanical parameters of surrounding rock and water content is determined. The micro mechanism of rheology of water bearing weakly cemented sandstone is studied. The dewatering technology inside tunnel in water bearing weakly cemented sandstone stratum is put forward. Abstract: Weakly cemented sandstone is widely distributed in Northwest China. Its mechanical properties decline after encountering water, resulting in engineering and technical problems such as excavation face collapse and initial support failure during tunnel excavation. On the basis of the Taoshuping and Humaling tunnel projects, this study evaluates the physical characteristics of water-bearing weakly cemented sandstone by indoor testing and analyzes the reasons for the difficulty of grouting in this stratum. The mechanical properties of water-bearing weakly cemented sandstone are determined, the microstructural characteristics of water-bearing weakly cemented sandstone are analyzed by scanning electron microscopy, and the weakening mechanism of water-bearing weakly cemented sandstone is clarified. On the basis of the aforementioned research and with the water stability of water-bearing weakly cemented sandstone considered, water-bearing weakly cemented sandstone tunnel dewatering technology was proposed and verified. This study addresses the problem of collapse shortly after tunnel excavation in the water-bearing weakly cemented sandstone stratum.